The knowledge management of work ability in collaboration with workplaces and occupational health services - Nissinen, Sari Päivikki; Soini, Satu; Palmgren, Helena (Finnish Journal of eHealth and eWelfare, 2021)
Employees' work ability can be supported by Occupational Health Collaboration between workplaces and Occupational Health Services. This requires fluent knowledge management of work ability, such as regular contacts and information exchange about employees' health and work ability. We examined Occupational Health professionals’ experiences of the knowledge management of work ability. The research material was collected through an electronic questionnaire which was sent to the contact persons of 454 Occupational Health units belonging to the OHS quality portal of Finnish Institute of Occupational Health between November and December 2020. The survey was answered by 86 Occupational Health professionals. The results were reported as quantities and percentages. Most of the respondents estimated that their multi-professional teams are competent in identifying work ability risks. Usually, the relevant work ability data were available, but not in the form in which the data were needed. Most often, the method of work ability information distribution had been agreed with the workplaces, but the ways of distribution should be further clarified. Managing knowledge of employees' work ability in the collaboration between Occupational Health Services and workplaces requires agreeing on procedures, in other words, what kind of information needs to be exchanged and in what ways, considering data protection and data security. When developing information systems for co-operation between occupational health care and the workplace, the aim has to be a structural documentation. Only this way the data can be utilized with no need to record it again in another system.